Dishcover Indonesia: Android Cooking Game on Indonesian Cuisine - Jeremy Jodi Widjaja (Journal of Games, Game Art, and Gamification, 2018)
The video game industry can be said to be one of the more modern undying industries that are ever growing and evolving. In Indonesia, there are several game development companies, however, there is currently no game that utilizes Indonesian cuisine as the main theme. It is also noted that there have been no recent cooking games that are unique nor a sequel. Currently, there is a gap in which consumers are not playing cooking games although they enjoy them. As a result, the author attempts to develop a game that can reach users’ expectations for a modern Android cooking game. Users were tested in two phases. Before the development, users were asked to rate their expectations of a cooking game and the current competition. After the development of the game, users were given the beta to test and rate their evaluation of the application. Based on the results of the two surveys, the game has achieved the results desired in the beginning of the project development.